Peculiarities of Stereotypes about Non-Verbal Communication and their Role in Cross-Cultural Interaction between Russian and Chinese Students - I A Novikova; M V Gridunova (Peoples' Friendship University of Russia (RUDN University), 2012)
The article is devoted to the analysis of the peculiarities of the stereotypes about non-verbal communication, formed in Russian and Chinese cultures. The results of the experimental research of the role of ethnic auto- and heterostereotypes about non-verbal communication in cross-cultural interaction between Russian and Chinese students of the Peoples' Friendship University of Russia are presented.